Tumor idyotipe as target antigen for multiple myeloma (Hematology Meeting Reports, 2009)
Early during development, pre-B cells become committed to the expression of a heavy and light chain Ig variable region. The heavy chain derives from the recombination of a variable (V) with a diversity (D) and a joining (J) region genes with a constant region (C). The V-D-J joints occur with a variable number of nucleotide insertions or deletions resulting in a unique sequence which creates the third hypervariable region (CDR III) and contributes to the antigen binding site. These antigenic regions (idiotype; Id) are characteristic for any given Ig producing tumor (i.e. multiple myeloma, MM; non-Hodgkin lymphoma; NHL) and can be recognized by an immune response consisting of anti-Id antibodies and/or by Id reactive T-cells.